Analisis Kemampuan Pemecahan Masalah Numerasi Siswa Berdasarkan Tingkat Kecemasan Matematis - Seftyana Ayu Susanti; Mega Teguh Budiarto; Rini Setianingsih (JRPM (Jurnal Review Pembelajaran Matematika), 2023)
The descriptive study analyzed the skills of vocational school students with low, medium, and high levels of mathematical anxiety in terms of their problem-solving abilities. It used a qualitative approach to examine the various mathematical content strands and scientific contexts of the learners. Its findings were based on the notion of the problem-solving stage by Polya, Newman,  as well as Krulik and Rudnik. The data collected during the study was gathered through a written test, which involved asking the participants to complete a questionnaire about their mathematical anxiety levels before they were asked to solve numeracy problems. The results of the study revealed that students with high levels of anxiety were more prone to experiencing problems with problem-solving. The findings of this study are valuable to mathematics educators and researchers. It is also expected to contribute to the development of effective problem-solving strategies for students.